2021
DOI: 10.2147/idr.s341357
|View full text |Cite
|
Sign up to set email alerts
|

Limited Polymorphism in Plasmodium falciparum Artemisinin Resistance Kelch13-Propeller Gene Among Clinical Isolates from Bushenyi District, Uganda

Abstract: Introduction Drug resistance remains a major challenge in malaria treatment, especially after the emergence of resistance to artemisinin-based combined therapies. Plasmodium falciparum Kelch13 gene mutations are implicated in conferring artemisinin resistance. Thus, this study was aimed at determining the occurrence of Kelch13 ( K13 ) propeller resistance gene polymorphism mutations in Bushenyi district, Uganda. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
2
4
1
Order By: Relevance
“…Our study found a 24% microscopy positivity for P. falciparum on day three, which could indicate a possible (35,36). A similar finding on the persistence of P. falciparum has been reported previously in AL-treated malaria patients in Uganda (30,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found a 24% microscopy positivity for P. falciparum on day three, which could indicate a possible (35,36). A similar finding on the persistence of P. falciparum has been reported previously in AL-treated malaria patients in Uganda (30,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 91%
“…Our study found a 24% microscopy positivity for P. falciparum on day three, which could indicate a possible emergence of partial artemisinin resistance (35,36). A similar finding on the persistence of P. falciparum has been reported previously in AL-treated malaria patients in Uganda (30,3739). Whether this is attributed to the development of resistance, especially the K13 mutation, or lack of adherence to AL has not been fully established.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, Further research and exploration into the specific mechanisms by which immunity may impact the dynamics of antimalarial drug response, especially in the context of delayed clearance, would provide valuable insights into the complexity of malaria resistance and treatment outcomes. The findings from the present study, which indicate a lack of mutation in the pfk13 propeller domain and limited polymorphism seen in [21] combined with observations from other studies in Kenya and Africa [25,26,27,28] revealing the majority of non-synonymous mutations which are not associated with delayed parasite clearance, collectively suggest that K13 may not be the most reliable predictive molecular marker for artemisinin resistance in Africa. These results emphasize the need for continued research to identify alternative molecular markers or factors that can better predict and understand the dynamics of artemisinin resistance in the African context.…”
Section: Discussioncontrasting
confidence: 57%
“…A similar finding on the persistence of P . falciparum has been reported previously in AL-treated malaria patients in Uganda [ 30 , 35 37 ]. Whether the persistence is attributed to the development of resistance, especially the K13 mutation, or lack of adherence to AL has not been fully established.…”
Section: Discussionmentioning
confidence: 76%